2018
DOI: 10.1080/00218464.2017.1396975
|View full text |Cite
|
Sign up to set email alerts
|

The use of acoustic emission and composite peel tests to detect weak adhesion in composite structures

Abstract: Adhesive bonding is one of the most promising joining technologies for composite aircraft. However, to comply with current aircraft certification rules, current safety-critical bonded joints, in which at least one of the interfaces requires additional surface preparation, are always used in combination with redundant mechanical fasteners, such as rivets and bolts. This lack of trust in bonded structures is mostly linked to the fear of lack of adhesion or a "weak bond".The aim of this paper is to tackle this ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 41 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Combined with the previous observation on the higher number of AE hits in the cohesive failure case, this suggests that AE events generated during adhesive failure have higher energies compared to the corresponding ones during cohesive failure. It is worth to be mentioned that Teixeira de Freitas et al observed the exact opposite (i.e., higher energy content in AE from cohesive failure) in DCB and peel tests, both dominated by normal stresses rather than shear stresses as in the stepped lap shear test case. This is verified by (Fig.…”
Section: Results and Analysismentioning
confidence: 93%
“…Combined with the previous observation on the higher number of AE hits in the cohesive failure case, this suggests that AE events generated during adhesive failure have higher energies compared to the corresponding ones during cohesive failure. It is worth to be mentioned that Teixeira de Freitas et al observed the exact opposite (i.e., higher energy content in AE from cohesive failure) in DCB and peel tests, both dominated by normal stresses rather than shear stresses as in the stepped lap shear test case. This is verified by (Fig.…”
Section: Results and Analysismentioning
confidence: 93%
“…Besides the contaminant removal, UV/ozone treatment is employed for the oxidation of the CFRP surface and the introduction of hydroxyl and carboxylic groups that would improve the interfacial adhesion [ 31 ]. Exposure times higher than 5 min were found to be successful in the introduction of a significant amount of oxygen containing functional groups in cured epoxy in printed circuit boards [ 32 , 33 , 34 , 35 ]. In addition, a significant increase in surface roughness was found due to the etching effect of UV/ozone treatment of epoxides [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Croccolo et al [4] use acoustic emission as condition monitoring technique for the evaluation of defect densities in adhesive bonding to predict the actual failure load of the adhesive joint. Some of these techniques, like acoustic emission are online methods for determining the damage progression in bonded joints and composites as reported by Cawley [5] and De Freitas [6] respectively. Such online methods enable to predict the onset and progression of damage under the mechanical load.…”
Section: Introductionmentioning
confidence: 99%